Analisis Kinerja Strategi Investasi Lump-Sum dan Dollar Cost Averaging pada Saham Indeks LQ-45 di Bursa Saham Indonesia Periode 2008-2009 - , Kusno Bari Joyo ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to analyze portfolio performance which applying lump-sum and dollar cost averaging investment strategies on the stocks in LQ-45 index for period 2008-2009. Implementation of the strategies in different market conditions, bearish (2008), bullish (2009) or both is expected to give investors view for a proper strategy to be applied in those market conditions. The study was conducted by simulating a lump-sum investment strategy (LS) and dollar cost averaging (DCA) in LQ-45 indexâs stock that have been selected. Using purposive sampling method, 12 stock in LQ-45 index with meet the criterias were selected as a samples. The simulation was conducted for the period of 2008, 2009 and 2008-2009 then HPR, mean return, and standar deviation calculated for each simulation period. Portfolio performance calculated using index Sharpe, Treynor and Jensen. The DCA was appropriate to be applied in 2008 as shown in the result that generated loss -33.61% less than LS strategy which generated loss -49.79% and less risky (in terms of standard deviation) of 13.64% compared to 14.22% resulted by LS strategy. The LS was appropriate to be applied in 2009 as shown in the result that generated return by 107.83% higher than the DCA strategy which generated return only 51.84% and give lower risk (in terms of standard deviation) by 8.64% compared to 9.00% resulted by DCA strategy. In 2008-2009, DCA strategies was appropriate to be applied as shown in the result that generated return by 47.38% higher than return generated by LS strategy which is 8.60% and resulting lower risk (in terms of standard deviation) by 12.71% compared to 13.04% resulted by LS strategy. Based on the Sharpe, Treynor and Jensenâs indexes, both portfolios in 2008 produced different rankings, however the DCA strategy portfolio has relatively lower risk than portfolio with LS strategy (in terms of standard deviation) and generate higher average of return. In 2009 based on the Sharpe, Treynor and Jensenâs index, both portfolio produced different rankings, however LS strategy portfolio has relatively lower risk than portfolio with DCA strategy (in terms of standard deviation) and generated higher average of return. Based on the Sharpe, Treynor and Jensenâs index, in the period 2008-2009 both portfolios produced different rankings, however the DCA strategy portfolio has relatively lower risk than portfolio with the LS strategy (in terms of standard deviation) and generated higher average of return.